Fiscal Thoughts and Their Evolution before the 19th Century: Analysis and Comparison between Britain and Germany - han, qing (Advances in Social Sciences Research Journal, 2020)
The tradition of English classical public finance thinks the government are out of the society and can intervene it. Base on former thought and the market failure theory, the mainstream public finance has a clear tendency to oppose the market and the government. This approach not only ignored the political functions of government but also cannot explain the PPP and NPM. The cameralism’s view of the government provided new ideas for explaining this issue. Through the analysis and comparison of the financial thoughts of Britain and Germany before the 19th century, this paper clarifies the evolutionary logic of British fiscal thought, compares the similarities and differences between the British and German financial thoughts. Besides this paper also discusses the roots of these two traditions view of the government. The fiscal theory of cameralism not only reflects the subjective initiative of the government but also conforms to the reality of our country. These traditions interdisciplinary research tendency should also be re-emphasized.